2012
DOI: 10.1177/0269215512442661
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sling and voluntary constraint during constraint-induced movement therapy for the arm after stroke: a randomized, prospective, single-centre, blinded observer rated study

Abstract: Voluntary activity constraint in the intact arm is equivalent to sling, standard constraint during massed practice of paretic arm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Forced use therapy was investigated in 6 RCTs (N=165)(59, 60, 65, 67-69, 79) (see supplementary web appendix 5) and did not show an added value for self-reported amount of arm-hand use in daily life and self-reported quality of arm-hand movement in daily life (Figure 2) (see also supplementary web appendix 6). …”
Section: Effects Of (M)cimtmentioning
confidence: 99%
See 1 more Smart Citation
“…Forced use therapy was investigated in 6 RCTs (N=165)(59, 60, 65, 67-69, 79) (see supplementary web appendix 5) and did not show an added value for self-reported amount of arm-hand use in daily life and self-reported quality of arm-hand movement in daily life (Figure 2) (see also supplementary web appendix 6). …”
Section: Effects Of (M)cimtmentioning
confidence: 99%
“…References: (a) 33-35, 37, 38, 43, 45, 46, 49, 50, 57, 62, 64, 70, 71, 73, 80, 82; (b) 39, 42; (c) 55, 73; (d) 46, 82; (e) 46, 75; (f) 28; (g) 31, 33- 43, 45- 47, 51-56, 73, 75-78, 80-82; (h) 28; (i) 34, 37, 41, 43, 46, 52, 54, 55, 57, 61-64, 70-73, 75, 77, 78, 80-82; (j) 67, 69; (k) 28; (l) 34, 36, 37, 41, 43, 46, 49-52, 54, 55, 57, 61, 62, 64, 70-73, 75, 77, 78, 80-82; (m) 67, 69, 79; (n) 41, 47, 52, 54, 62-64, 66, 71; (o) 53, 81, 82; (p) 81, 82.…”
Section: Figurementioning
confidence: 99%
“… 45 A mCIMT study with random assignment comparing protocols with and without restraint in 24 patients found similar motor improvements after a one-year follow-up. 46 A recent study, 47 evolving 47 participants, showed no difference between two groups of post stroke patients treated with a combination of CIMT and physiotherapy plus different constraint regimens (sling versus voluntary constraint). It seems that using a sling were not an advantage over voluntary constraint.…”
Section: Discussionmentioning
confidence: 98%
“…뇌졸중은 암, 심장병과 함께 주요 사망 원인의 하나로써 유병률이 점차 증가하고 있으며, 생존율은 높아지고 있으 나 기능 장애로 인한 많은 치료비가 지불되고 있다 1,2) . 뇌 의 병변 부위에 따라 손상된 뇌의 반대쪽에 감각 및 운동 장애와 같은 신경학적 손상을 일으키며, 특히 뇌졸중으로 인한 운동결함은 뇌 손상 반대쪽 신체에 발생하는 편마비 가 나타난다 3,4) . 또한 이러한 근육의 약화와 운동기능의 손상으로 인하여 팔다리의 움직임이 감소되고 일생상활 을 어렵게 한다 5,6) .…”
Section: 서론»»»unclassified